The effect of high temperature on compressive strength and splitting tensile strength of structural lightweight concrete containing fly ash - Tanyildizi, Harun; Coskun, Ahmet (Elsevier Sci Ltd, 2008)
In this study, the effect of high temperature on compressive and splitting tensile strength of lightweight concrete containing fly ash was investigated experimentally and statistically. The mixes incorporating 0%, 10%, 20% and 30% fly ash were prepared. After being heated to temperatures of 200, 400 and 800 degrees C, respectively, the compressive and splitting tensile strength of lightweight concrete was tested. This article adopts Taguchi approach with an L-16 (4(5)) to reduce the numbers of experiment. Two control factors (percentage of fly ash and heating degree) for this study were used. The level of importance of these parameters on compressive and splitting tensile strength was determined by using analysis of variance (ANOVA) method. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: lightweight concrete; mechanical properties; high temperature; fly ash; analysis of variance (ANOVA)